Knee joint position sense and kinematic control in relation to motor competency in 13 to 14-year-old adolescents - Liu, Y; Esser, P; Weedon, BD; Springett, D; Joshi, S; Tsou, M; Wang, R; Dawes, H (BioMed Central, 2024)
Background: Motor competence (MC) is a key component reflecting one’s ability to execute motor tasks and is an important predictor of physical fitness. For adolescents, understanding the factors affecting MC is pertinent to their development of more sophisticated sporting skills. Previous studies considered the influence of poor proprioceptive ability on MC, however, the relationship between lower limb joint position sense, kinematic control, and MC is not well understood. Therefore, the aim of this study was to determine the relation between joint position sense and kinematic control with MC in adolescents during a lower limb movement reproduction task. Methods: This study was a cross-sectional design. Young people (n = 427, 196 girls and 231 boys) aged 13 to 14 years were recruited. A movement reproduction task was used to assess joint position sense and kinematic control, while the Movement Assessment Battery for Children (mABC-2) was used to assess MC. In this study, participants were categorized into the Typically Developed (TD, n = 231) and Probable Developmental Coordination Disorder (DCD, n = 80) groups for further analysis of joint position sense, kinematic control, and MC between groups. Results: Kinematic data, specifically normalized jerk, showed a significant correlation with MC. There was no correlation between knee joint position sense and MC, and no group differences between DCD and TD were found. Conclusions: Joint position sense should not be used as a measure to distinguish TD and DCD. Rather than joint position sense, control of kinematic movement has a greater influence on the coordination of the lower limbs in adolescents. Movement control training should be implemented in the clinical setting to target kinematic control, rather than focus on joint position sense practice, to improve motor competency. Trial Registration Identifier: NCT03150784. Registered 12 May 2017, https://clinicaltrials.gov/study/NCT03150784.